2020
DOI: 10.1126/scisignal.aay3258
|View full text |Cite
|
Sign up to set email alerts
|

An interspecies translation model implicates integrin signaling in infliximab-resistant inflammatory bowel disease

Abstract: Anti–tumor necrosis factor (anti-TNF) therapy resistance is a major clinical challenge in inflammatory bowel disease (IBD), due, in part, to insufficient understanding of disease-site, protein-level mechanisms. Although proteomics data from IBD mouse models exist, data and phenotype discrepancies contribute to confounding translation from preclinical animal models of disease to clinical cohorts. We developed an approach called translatable components regression (TransComp-R) to overcome interspecies and trans-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…To perform cross-species analysis, we utilized a modified version of the translatable component regression (TransComp-R) modeling methodology ( Brubaker et al, 2020 ). The integrative analysis tool involves a multi-part workflow that is conceptually illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To perform cross-species analysis, we utilized a modified version of the translatable component regression (TransComp-R) modeling methodology ( Brubaker et al, 2020 ). The integrative analysis tool involves a multi-part workflow that is conceptually illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that many of our findings could be validated in RNA-sequencing datasets and that additional signatures beyond the limit of detection for microarray data could be inferred using RNA-sequencing datasets. Additionally, the initial TransComp-R study ( Brubaker et al, 2020 ) involved concomitant analysis of proteomic and transcriptomic data. This study demonstrated that TransComp-R is effective for other omics data not highlighted in our study, as the computational workflow does not mathematically preclude its application to various data types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, the need for a deep and rigorous biological assessment in early phase clinical trials (similar to what may occur in preclinical studies) has been less emphasized and seldom put into practice [32][33][34][35][36] . This is surprising since a major leap in the entire drug development pipeline (the transition from animal to human biology) takes place when early phase trials are initiated 37 (interestingly, to help cope with these difficulties, interspecies translation models are under development in autoimmune diseases 38 ).…”
Section: Importance Of Exmtsmentioning
confidence: 99%